Enhancing visual motion discrimination by desynchronizing bifocal oscillatory activity - SALAMANCA-GIRON, Roberto F.; RAFFIN, Estelle; ZANDVLIET, Sarah B.; SEEBER, Martin; MICHEL, Christoph M.; SAUSENG, Paul; HUXLIN, Krystel R.; HUMMEL, Friedhelm C. (NeuroImage (Orlando, Fla.), 2021)
Visual motion discrimination involves reciprocal interactions in the alpha band between the primary visual cortex (V1) and mediotemporal areas (V5/MT). We investigated whether modulating alpha phase synchronization using individualized multisite transcranial alternating current stimulation (tACS) over V5 and V1 regions would improve motion discrimination. We tested 3 groups of healthy subjects with the following conditions: (1) individualized In-Phase V1alpha-V5alpha tACS (0° lag), (2) individualized Anti-Phase V1alpha-V5alpha tACS (180° lag) and (3) sham tACS. Motion discrimination and EEG activity were recorded before, during and after tACS. Performance significantly improved in the Anti-Phase group compared to the In-Phase group 10 and 30 min after stimulation. This result was explained by decreases in bottom-up alpha-V1 gamma-V5 phase-amplitude coupling. One possible explanation of these results is that Anti-Phase V1alpha-V5alpha tACS might impose an optimal phase lag between stimulation sites due to the inherent speed of wave propagation, hereby supporting optimized neuronal communication. •Alpha multisite (V1 and V5) tACS influences global motion discrimination and integration in a phase dependent manner.•Improvement in motion discrimination was associated with decreased phase-amplitude coupling in the alpha and gamma band between V1 and V5.